Strategi Pemasaran Untuk Meningkatkan Daya Tarik Pengunjung Terhadap Mall Area Galuh Mas - Cindy Noerbani (Pusat Riset dan Inovasi Nasional, 2023)
The establishment of a shopping center or what is often called a mall is the impact of advancing times, technology and the development of an area. Mall has now become an identity to increase social status. This research starts from the phenomenon of the rise of malls in Galuh Mas. This study discusses the strategy adopted by the management office of PT Galuh Citarum which houses 3 malls in the Galuh Mas area to increase the number of visitors. The purpose of this research is to find out how the marketing strategy is to increase the number of visitors. This research includes qualitative research. By collecting data through interviews. The results of this study are the marketing communication strategies of mall managers referring to several elements of Integrated Marketing Communication (IMC). Because IMC has an important role to increase visitor traffic. These elements are events, advertising, sales promotion, public relations, personal selling and direct marketing. And by using SWOT analysis, it can be based on logic that can maximize strengths and opportunities, but simultaneously can minimize weaknesses and threats.